STUDI MOLEKUL n2P2 DENGAN GRUP SIMETRI D h MENGGUNAKAN METODE AB INITIO - Devita, Liza (IAIN Batusangkar, 2014)
This research theoretically describes the molecule n2 p2 with cemetery group d-h using ab initio /STO-3 G that is included in the package of HyperChem Pro.6.0. this study also discusses the effect of atom toward electronic features and the structure that is formed from molecule n2 p2. Moreover, this research investigated the effect of cemetery group n1-P2 toward molecule stability n2 P2. Research findings revealed that loop n1-P2 or loop P2-P3 could be single loop, double loop, and even triple loop. For the optimum result, the most stable molecule was CIP (E=993242,9375), that is the optimum result of CIPPCI. However, the most unstable molecule was PP (E=423494,6563), that is the optimum result of HPPH. In one group from top-down or in a period form left-right, total energy seems decrease. In other words, n2 P2 was seen more stable. Key wordS :Ab initio, molekul n2P2, grup simetri D h